Peran Sosiologi Pendidikan Islam dalam Membentuk Karakter Peserta Didik : Tinjauan Literatur Review - Nirmala Dwi Liestyo Utomo; Nurhamidah Nurhamidah; Aynunis Zahrotul Jannah; Amira Khansa Nabila; Mualimin Mualimin (Reflection : Islamic Education Journal, 2024)
This study aims to comprehensively analyze the role of Islamic educational sociology in shaping the character of students through a systematic literature review. The results show that Islamic educational sociology offers a rich conceptual framework, including the paradigm of multicultural Islamic education, the integration of spiritual and social values, and a holistic approach to character building. The implementation of the concepts of Islamic educational sociology in character education practice covers aspects of management, the role of teachers, and specific strategies. The effectiveness of this approach is seen in its significant contribution to character development, both at the individual and institutional levels. The synergy between local culture and Islamic education also demonstrates the potential of the Islamic educational sociology approach in shaping a strong national character. However, further research is needed to explore the adaptation of this approach in addressing contemporary challenges.